Vanadium oxide-based porous ceramic composite material and preparation method thereof

By using vanadium pentoxide, graphite powder, steel slag, starch and binder, the vanadium oxide-based porous ceramic composite material is solved, and the existing vanadium oxide synthesis process is complicated and recycling difficulties is difficult, achieving efficient removal of methylene blue and reducing the preparation cost.

CN119707522APending Publication Date: 2025-03-28PANZHIHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410277263.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-11
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing vanadium oxide synthesis process is complex, the preparation cost is high, the performance of removing methylene blue is limited, and they are all used in powder form, making recycling and recycling difficult.

Method used

Vanadium pentoxide, graphite powder, steel slag, starch and binder are used as raw materials, and porous ceramic composite materials are prepared through two steps of preparation of mixture and reducing and firing. The process of this method is simple, absorbs metallurgical solid waste, reduces costs, and improves the adsorption performance of the material.

Benefits of technology

The prepared vanadium oxide-based porous ceramic composite material has good adsorption rate and adsorption amount, is suitable for wastewater treatment in the textile industry, is easy to recycling, and improves production efficiency and economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707522A_ABST
    Figure CN119707522A_ABST
Patent Text Reader

Abstract

The invention relates to a vanadium oxide-based porous ceramic composite material and a preparation method thereof, and belongs to the technical field of porous ceramic composite materials. The technical problem to be solved by the invention is to provide the preparation method of the vanadium oxide-based porous ceramic composite material. The method comprises the following steps: a, uniformly mixing vanadium pentoxide, graphite powder, steel slag, starch and a binder according to a weight ratio of 1: 1: 4: (0.5-2.5): 1, tabletting, and drying to obtain a dry flaky mixture; and b, carrying out reduction roasting on the flaky mixture, and naturally cooling after roasting is finished, thereby obtaining the product. The porous ceramic composite material is prepared by adopting a one-step method, the process is simple, a large amount of metallurgical solid waste is consumed while the cost is saved, and the production efficiency, the economic benefit and the social benefit are improved. The vanadium oxide-based porous ceramic composite material prepared by the method is simple to recover and recycle, has good adsorption performance, can adsorb methylene blue, is used for treatment of textile industry sewage, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a vanadium oxide-based porous ceramic composite material and a preparation method thereof, belonging to the technical field of porous ceramic composite materials. Background Art

[0002] In recent years, as the industry has entered a stage of rapid and high-quality development, environmental pollution prevention and control, especially water pollution prevention and control, has received high and widespread attention. The textile industry accounts for about 10% of industrial wastewater discharge, which in turn causes synthetic dyes to eventually enter the environment directly. Due to the complex chemical structure of synthetic dyes, they have strong resistance to biodegradation. Methylene blue (MB) is one of the typical representatives of synthetic dyes and is often used as a target for removal in the photocatalytic and adsorption processes of materials.

[0003] At present, vanadium oxides and their composites as photocatalysts and adsorbents for the photocatalytic degradation and adsorption of methylene blue solutions have become one of the research hotspots. The researchers found that V4O7, V2O5 and V2O3 synthesized by hydrothermal method have good photocatalytic degradation performance for methylene blue; Li et al. (Flexible 3D Fe@VO2 core-shell mesh: A highly efficient and easy-recycling catalyst for the removal of organic dyes, Science of The Total Environment, 2018, 637–638: 825) prepared a mesh Fe@VO2 composite material by electrodeposition, Chen et al. (The Improved Photocatalytic Properties of Methylene Blue for V2O3 / CNT / TiO2 Composite under Visible Light, International Journal of Photoenergy, 2010, Article ID 264831) prepared a V2O3 / CNT / TiO2 composite material by sol-gel method, Bayati et al. (Photo-Degradation of Methelyne Blue over V2O5–TiO2 Nano-Porous Layers Synthesized by Micro Arc Oxidation, Catalysis Letters, 2010, 134: 162) V2O5 / TiO2 nanoporous materials prepared by micro-arc oxidation method, and Manh et al. (Synthesis of Nano-Urchin Mo-Doped VO2 Particles by the Hydrothermal Method, Journal of Applied Spectroscopy, 2020, 87(1): 22) Mo / VO2 composite materials synthesized by hydrothermal method both showed good photocatalytic removal ability for methylene blue.Saghi et al. (Vanadium oxide nanoparticles for methylene blue water remediation: Exploring the effect of physicochemical parameters by process modeling, Journal of Applied Spectroscopy, 2020, 87(1): 22) and Nahid et al. (Vanadium dioxidenanoparticles as a promising sorbent for controlled removal of waterbornefluoroquinolone ciprofloxacin, Journal of Molecular Liquids, 2020, 318: 114046) synthesized nano VO2 particles by hydrothermal method and studied their adsorption properties for methylene blue and ciprofloxacin.

[0004] However, the current vanadium oxide synthesis process is complex, the preparation cost is high, the performance of removing methylene blue is limited, and it is all used in the form of powder, which makes recovery and recycling difficult. Summary of the invention

[0005] In view of the above defects, the technical problem solved by the present invention is to provide a method for preparing a vanadium oxide-based porous ceramic composite material.

[0006] The method for preparing the vanadium oxide-based porous ceramic composite material of the present invention comprises the following steps:

[0007] a. Preparing a mixture: mixing vanadium pentoxide, graphite powder, steel slag, starch and a binder in a weight ratio of 1:1:4:0.5-2.5:1, tableting, and drying to obtain a dry flaky mixture;

[0008] b. Reduction roasting: The flaky mixture is subjected to reduction roasting, and then naturally cooled after roasting to obtain a roasted product.

[0009] In some embodiments of the present invention, in step a, the binder is a polyvinyl alcohol solution with a mass concentration of 5 to 7%.

[0010] In some specific embodiments, in step a, the composition of the steel slag includes the following components in parts by weight: 5 to 10 parts of MgO, 3 to 6 parts of Al2O3, 10 to 15 parts of SiO2, 1 to 2 parts of P2O5, 40 to 45 parts of CaO, 20 to 30 parts of Fe2O3, 0.5 to 1 part of TiO2, and 0.5 to 1 part of MnO.

[0011] In a specific embodiment, in step a, the composition of the steel slag includes the following components: MgO 7.08%, Al2O3 5.29%, SiO2 13.60%, P2O5 1.35%, CaO 42.10%, Fe2O3 26.70%, TiO2 0.91%, and MnO0.92%.

[0012] In some specific embodiments, in step a, the pressure parameter of the powder tablet press is 5-10 MPa.

[0013] In some specific embodiments, in step a, the drying temperature is 120-150° C., and the drying time is 2-2.5 h.

[0014] In some specific embodiments, in step b, the reduction roasting temperature is 650° C. to 750° C., and the reduction roasting time is 2 to 3 hours.

[0015] In some specific embodiments, in step b, the crucible used for calcination is a graphite crucible, and the upper and lower parts of the dry flaky mixture are covered with 1-2 cm thick graphite powder. After calcination, the mixture is immediately taken out and cooled to obtain a porous ceramic composite material.

[0016] The present invention also provides a vanadium oxide-based porous ceramic composite material prepared by the method of the present invention.

[0017] The vanadium oxide-based porous ceramic composite material of the present invention is prepared by the preparation method of the vanadium oxide-based porous ceramic composite material of the present invention. The material has a porous structure, is easy to recycle, has a good adsorption rate and adsorption amount for methylene blue, and can be used in textile industrial wastewater treatment.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The present invention provides a method for preparing a vanadium oxide-based porous ceramic composite material with adsorption performance, which has a simple process, saves costs and absorbs a large amount of metallurgical solid waste, thereby improving production efficiency, economic benefits and social benefits, and can fully utilize the rich vanadium resources in the Panxi area to achieve high-value application of resources.

[0020] The vanadium oxide-based porous ceramic composite material of the invention has a good adsorption rate and adsorption amount for methylene blue, can be used in textile industrial wastewater treatment, has great potential in large-scale organic pollutant adsorption applications, and is easy to recycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 1 is the XRD diagram of the vanadium oxide-based porous ceramic composite material prepared in Examples 1 to 4 of the present invention.

[0022] Figure 2 The XPS narrow spectra of vanadium element of the vanadium oxide-based porous ceramic composite materials prepared in Examples 1, 3 and 4 of the present invention.

[0023] Figure 3 This is a process flow chart for preparing the vanadium oxide-based porous ceramic composite material in Examples 1 to 4 of the present invention. DETAILED DESCRIPTION

[0024] The method for preparing the vanadium oxide-based porous ceramic composite material of the present invention comprises the following steps:

[0025] a. Preparing a mixture: mixing vanadium pentoxide, graphite powder, steel slag, starch and a binder in a weight ratio of 1:1:4:0.5-2.5:1, tableting, and drying to obtain a dry flaky mixture;

[0026] b. Reduction roasting: The flaky mixture is subjected to reduction roasting, and then naturally cooled after roasting to obtain a roasted product.

[0027] The method of the present invention uses vanadium pentoxide, graphite powder, steel slag, starch and a binder as raw materials to prepare a porous ceramic composite material in one step. The preparation process is simple, and the cost is saved while absorbing a large amount of metallurgical solid waste, thereby improving production efficiency, economic benefits and social benefits. The vanadium oxide-based porous ceramic composite material prepared in this way is easy to recycle and recycle, has good adsorption performance, can adsorb methylene blue, and is used in the treatment of textile industrial wastewater, and has good application prospects.

[0028] The various raw materials of the porous ceramic composite material of the present invention can cooperate with each other to enhance synergy. Among them, graphite powder plays the role of a reducing agent in the reduction roasting process, and can reduce vanadium pentoxide to vanadium trioxide and vanadium dioxide with stronger adsorption capacity. In addition, since graphite powder has a lamellar structure and a large specific surface area, it can improve the overall adsorption capacity of the composite material; steel slag plays a skeleton role in the composite material due to its high melting point and stable physical and chemical properties; starch plays the role of a porogen, and the content of starch can adjust the porosity of porous ceramics; the role of the binder is to enhance the molding ability of the mixture of various raw materials at room temperature, thereby providing a basis for obtaining a porous ceramic composite material. These materials complement each other and are indispensable.

[0029] The binder may be any conventional binder in the art. In some embodiments of the present invention, in step a, the binder is a polyvinyl alcohol solution with a mass concentration of 5 to 7%.

[0030] In some specific embodiments, in step a, the composition of the steel slag includes the following components in parts by weight: 5 to 10 parts of MgO, 3 to 6 parts of Al2O3, 10 to 15 parts of SiO2, 1 to 2 parts of P2O5, 40 to 45 parts of CaO, 20 to 30 parts of Fe2O3, 0.5 to 1 part of TiO2, and 0.5 to 1 part of MnO.

[0031] In a specific embodiment, in step a, the composition of the steel slag includes the following components in weight percentage: MgO 7.08%, Al2O3 5.29%, SiO2 13.60%, P2O5 1.35%, CaO 42.10%, Fe2O3 26.70%, TiO20.91%, and MnO 0.92%.

[0032] In some specific embodiments, in step a, the pressure parameter of the powder tablet press is 5-10 MPa.

[0033] In some specific embodiments, in step a, the drying temperature is 120-150° C., and the drying time is 2-2.5 h.

[0034] In some specific embodiments, in step b, the reduction roasting temperature is 650° C. to 750° C., and the reduction roasting time is 2 to 3 hours.

[0035] In some specific embodiments, in step b, the crucible used for calcination is a graphite crucible, and the upper and lower parts of the dry flaky mixture are covered with 1-2 cm thick graphite powder. After calcination, the mixture is immediately taken out and cooled to obtain a porous ceramic composite material.

[0036] The present invention also provides a vanadium oxide-based porous ceramic composite material prepared by the method of the present invention.

[0037] The vanadium oxide-based porous ceramic composite material of the present invention is prepared by the preparation method of the vanadium oxide-based porous ceramic composite material of the present invention. The material has a porous structure, is easy to recycle, has a good adsorption rate and adsorption amount for methylene blue, and can be used in textile industrial wastewater treatment.

[0038] The following is a detailed description of the embodiments of the present invention in conjunction with specific examples, but those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out under conventional conditions. The steel slag components used in the examples are: MgO 7.08%, Al2O3 5.29%, SiO213.60%, P2O5 1.35%, CaO 42.10%, Fe2O3 26.70%, TiO2 0.91%, MnO 0.92%; vanadium pentoxide, graphite powder and starch are all analytically pure. The binder used in the examples is a polyvinyl alcohol solution with a mass fraction of 5%.

[0039] Example 1

[0040] Vanadium pentoxide, graphite powder, steel slag, starch and binder are mixed in a weight ratio of 1:1:4:0.5:1 to obtain a mixture; the mixture is pressed into shape using a powder tablet press at a molding pressure of 5 MPa; the flaky mixture is dried at 120°C for 2 hours using an electric heated blast drying oven to obtain a dry flaky mixture; the dry flaky mixture is placed in a graphite crucible, and the upper and lower parts of the dry flaky mixture are covered with 1 cm thick graphite powder; the graphite crucible containing the dry flaky mixture is placed in a high-temperature electric furnace, and roasted at 700°C for 2.5 hours. After the roasting is completed, the material is immediately taken out and cooled to obtain a vanadium oxide-based porous ceramic composite material.

[0041] The porosity of the sample was tested using an electronic density meter. The porosity of the sample in this example was 11.70%.

[0042] The adsorption conditions are as follows: at room temperature, 1.9 g of the porous ceramic composite material prepared in this example was added to 100 mL of methylene blue solution (concentration of 10 mg / L), and adsorbed for 8 hours at an oscillation rate of 150 times / min. The removal rate of methylene blue by the porous ceramic composite material prepared in this example was 40.68%, and the adsorption amount was 0.21 mg / g.

[0043] The adsorption amount and removal rate of methylene blue by the porous ceramic composite material are calculated according to formula (1) and formula (2), respectively.

[0044]

[0045]

[0046] Where: q t is the adsorption amount at time t, mg / g; R t is the removal rate at time t, %; C0 is the initial concentration of MB solution, mg / L; C tis the concentration of MB solution at time t, mg / L; m is the amount of porous ceramic composite material, g; V is the volume of MB solution, L.

[0047] Example 2

[0048] Vanadium pentoxide, graphite powder, steel slag, starch and binder are mixed in a weight ratio of 1:1:4:1:1 to obtain a mixture; the mixture is pressed into shape using a powder tablet press at a molding pressure of 5 MPa; the flaky mixture is dried at 120°C for 2 hours using an electric heated blast drying oven to obtain a dry flaky mixture; the dry flaky mixture is placed in a graphite crucible, and the upper and lower parts of the dry flaky mixture are covered with 1 cm thick graphite powder; the graphite crucible containing the dry flaky mixture is placed in a high-temperature electric furnace, and roasted at 700°C for 2.5 hours. After the roasting is completed, the material is immediately taken out and cooled to obtain a vanadium oxide-based porous ceramic composite material.

[0049] The porosity of the sample was tested using an electronic density meter. The porosity of the sample in this example was 20.70%.

[0050] The adsorption conditions are as follows: at room temperature, 1.8 g of the porous ceramic composite material prepared in this example was added to 100 mL of methylene blue solution (concentration of 10 mg / L), and adsorbed for 8 hours at an oscillation rate of 150 times / min. The removal rate of methylene blue by the porous ceramic composite material prepared in this example was 36.53%, and the adsorption amount was 0.20 mg / g.

[0051] Example 3

[0052] Vanadium pentoxide, graphite powder, steel slag, starch and binder are mixed in a weight ratio of 1:1:4:1.5:1 to obtain a mixture; the mixture is pressed into shape using a powder tablet press at a molding pressure of 5 MPa; the flaky mixture is dried at 120°C for 2 h using an electric heated blast drying oven to obtain a dry flaky mixture; the dry flaky mixture is placed in a graphite crucible, and the upper and lower parts of the dry flaky mixture are covered with 1 cm thick graphite powder; the graphite crucible containing the dry flaky mixture is placed in a high-temperature electric furnace, and roasted at 700°C for 2.5 h. After the roasting is completed, the material is immediately taken out and cooled to obtain a vanadium oxide-based porous ceramic composite material.

[0053] The porosity of the sample was tested using an electronic density meter. The porosity of the sample in this example was 24.50%.

[0054] The adsorption conditions are as follows: at room temperature, 2.0 g of the porous ceramic composite material prepared in this example was added to 100 mL of methylene blue solution (concentration of 10 mg / L), and adsorbed for 8 hours at an oscillation rate of 150 times / min. The removal rate of methylene blue by the porous ceramic composite material prepared in this example was 35.45%, and the adsorption amount was 0.18 mg / g.

[0055] Example 4

[0056] Vanadium pentoxide, graphite powder, steel slag, starch and binder are mixed in a weight ratio of 1:1:4:2.5:1 to obtain a mixture; the mixture is pressed into shape using a powder tablet press at a molding pressure of 5 MPa; the flaky mixture is dried at 120°C for 2 hours using an electric heated blast drying oven to obtain a dry flaky mixture; the dry flaky mixture is placed in a graphite crucible, and the upper and lower parts of the dry flaky mixture are covered with 1 cm thick graphite powder; the graphite crucible containing the dry flaky mixture is placed in a high-temperature electric furnace, and roasted at 700°C for 2.5 hours. After the roasting is completed, the material is immediately taken out and cooled to obtain a vanadium oxide-based porous ceramic composite material.

[0057] The porosity of the sample was tested using an electronic density meter. The porosity of the sample in this example was 46.3%.

[0058] The adsorption conditions are as follows: at room temperature, 2.1 g of the porous ceramic composite material prepared in this example was added to 100 mL of methylene blue solution (concentration of 10 mg / L), and adsorbed for 8 hours at an oscillation rate of 150 times / min. The removal rate of methylene blue by the porous ceramic composite material prepared in this example was 41.47%, and the adsorption amount was 0.20 mg / g.

Claims

1. A method for preparing a vanadium oxide-based porous ceramic composite material, characterized in that: The following steps are involved: a. Preparing a mixture: mixing vanadium pentoxide, graphite powder, steel slag, starch and a binder in a weight ratio of 1:1:4:0.5-2.5:1, tableting, and drying to obtain a dry flaky mixture; b. Reduction roasting: The flaky mixture is subjected to reduction roasting, and then naturally cooled after roasting to obtain a roasted product.

2. The method for preparing the vanadium oxide-based porous ceramic composite material according to claim 1, characterized in that: In step a, the binder is a polyvinyl alcohol solution with a mass concentration of 5-7%.

3. The method for preparing the vanadium oxide-based porous ceramic composite material according to claim 1, characterized in that: In step a, the composition of the steel slag includes the following components in parts by weight: 5 to 10 parts of MgO, 3 to 6 parts of Al2O3, 10 to 15 parts of SiO2, 1 to 2 parts of P2O5, 40 to 45 parts of CaO, 20 to 30 parts of Fe2O3, 0.5 to 1 part of TiO2, and 0.5 to 1 part of MnO.

4. The method for preparing the vanadium oxide-based porous ceramic composite material according to claim 3, characterized in that: In step a, the composition of the steel slag includes the following components: MgO 7.08%, Al2O3 5.29%, SiO2 13.60%, P2O51.35%, CaO 42.10%, Fe2O3 26.70%, TiO2 0.91%, and MnO 0.92%.

5. The method for preparing the vanadium oxide-based porous ceramic composite material according to claim 1, characterized in that: In step a, the pressure parameter of the powder tablet press is 5 to 10 MPa.

6. The method for preparing the vanadium oxide-based porous ceramic composite material according to claim 1, characterized in that: In step a, the drying temperature is 120-150° C. and the drying time is 2-2.5 hours.

7. The method for preparing the vanadium oxide-based porous ceramic composite material according to claim 1, characterized in that: In step b, the reduction roasting temperature is 650° C. to 750° C., and the reduction roasting time is 2 to 3 hours.

8. The method for preparing the vanadium oxide-based porous ceramic composite material according to claim 1, characterized in that: In step b, the crucible used for calcination is a graphite crucible, and the upper and lower parts of the dried flaky mixture are covered with 1-2 cm thick graphite powder. After the calcination is completed, the mixture is immediately taken out and cooled to obtain a porous ceramic composite material. 9 . The vanadium oxide-based porous ceramic composite material prepared by the method for preparing the vanadium oxide-based porous ceramic composite material according to any one of claims 1 to 8 .